Formal institutions – The source of unproductive entrepreneurship in Poland - Piotr Dominiak; Julita E. Wasilczuk (Gdańsk University of Technology, Faculty of Management and Economics, 2017)
Objective: The purpose of this article is to determine the entrepreneurs' perception of formal institutions in Poland as a source of non-productive behaviours. Research Design & Methods: The research methodology was developed based on many years of the teams' research experience. It involved three stages of research: 1) panel of experts and 2) telephone surveys of 1,612 entrepreneurs in Poland, which were the basis for 3) development of detailed research to be conducted among 300 entrepreneurs. Findings: The Polish entrepreneurs are mostly forced to unproductivity and they rather do not use the institutions to fight off the competition (offensive, voluntary unproductivity). The entrepreneurs themselves do not seem to provide much evidence for the unproductivity caused by the formal institutions. Implications & Recommendations: The study revealed a number of shortcomings in the research methodology itself. Conducting the research on a larger group of respondents necessitated the development of a standard questionnaire which does not capture all the shades of unproductivity. Perhaps individual interviews with entrepreneurs would allow for describing the activities treated as voluntary unproductivity. Contribution & Value Added: The original contribution of the authors is the division of unproductive entrepreneurship into voluntary and forced. So far no studies of this type have been conducted in Poland.
Keywords: P48; M21; L25; D22; 330; unproductive entrepreneurship; formal institutions; institutional economics